PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PERAWAT RSUD. HAULUSSY AMBON - Sahertian, Olivia Laura (Arthavidya Jurnal Ilmiah Ekonomi, 2013)
Organization member behavior determinesuccessfulness of hospital. Extra role behavior can increase organization performance by efficiency and effective in organization practice. Basic of extra role behavior is being conceptualized become Organizational Citizenship Behavior/ OCB. Some antecedent that can influence organization members to show the Organizational Citizenship Behavior is job satisfaction and organizational commitment.This research purpose is to analyze job satisfaction and organizational commitment towards Organizational Citizenship Behavior. The research conduct in RSUD dr. Haulussy Ambon, especially to nurse, the sample consist of 174 people as respondent. Data collected by questionnaire, interview and documentation, next the data in manner by using descriptive analysis and multiple regression.The analyze result show thatjob satisfactionand organizational commitmentsimultaneously significantly impactOrganizational Citizenship Behavior. The results from the partial test shown thatjob satisfaction and organizational commitmentsignificantly impactOrganizational Citizenship Behavior. Implication of this research to RSUD dr. Haulussy Ambon, it is the side of hospital can increased OCB nurse with increasing job satisfaction and nurse organizational commitment.Key Words : Job Satisfaction, Organizational Commitment, OrganizationalCitizenship Behavior (OCB)